(untitled) (Journal of Educational Sciences, 2017)
The features and principles of the educational system for the training of creative personnel are still out of sight in the development of regulations governing the activities of educational institutions of culture and art. For the speedy integration of the higher education system of the country in the international educational environment in a dynamically changing world, it is necessary to improve responsibility for the quality of education in each institution and, consequently, to change approaches to managing educational organizations. In our, the crisis in the management of education are mirrored in the field of arts and culture in creasingly. Moreover, it can be outlined that, in these areas this phenomena are felt with particular acuteness. There is not can be ignored that the institutions of art (specializing in music, theater, visual and other arts) have certain specificity. Our integration with the developed countries in the field of education must be accompanied by a preservation-established for decades and proven systems and approaches in the field of performing arts training. It is important that in connection with the accession to the Bologna Process musical education of the country has not lost its inherent consistency, continuity, professional thoroughness, practical orientation of the students’ knowledge and skills and, consequently, the competitiveness in the international. The phenomenon of art leaves its mark on the educational process (teaching staff, students), and the style of interpersonal relationships in the creative teams, and much more. Mean while, this factis of ten not taken in to account